Aplikasi Monitoring Pada Tanaman Aglaonema menggunakan IOT - Liyyin Putra Arif Wicaksana; Alexander Setiawan; Resmana Lim (Universitas Kristen Petra, 2022)
Aglaonema plants are quite difficult to cultivate because the keeper must know what Aglaonema plants need in order to thrive and be beautiful. Aglaonema plants have high sensitivity to roots and stems, as well as leaves. Aglaonema plants require a soil moisture level that is not too moist and not too dry, a soil pH of 6-7, and a placement that is not exposed to direct sunlight. The solution is made by utilizing advanced technology which makes an application that can monitor and maintain the fertility of soil conditions on the Aglaonema plant on a mobile basis and use IOT as a sensor tool to retrieve data which will later be sent to the android application. The trial was carried out by using 2 aglaonema plants to be treated simultaneously. Plant 1 will be treated by volunteers who have just touched Aglaonema so that it provides care like other plants in general, plant 2 will be treated using a monitoring application, trials are also carried out by adjusting the data obtained from aglaonema experts. From the test results, it was found that the effectiveness of the application in monitoring Aglaonema plants has an accuracy rate of 100%.